An Analysis of Directive Speech Act in the“A Man Called Otto” Movie - Tharissha Pramudita; Agus Triyogo; Ayu Oktaviani (Institut Nalanda, 2025)
The objective of this research was to describe he types of directive speech act found A Man Called Otto movie. The method applied in this research was designed in qualitative descriptive. This research used human instrument by herself. The data was analyzed by describing the type of directive speech act in a movie. In collecting the data, the researcher watched A Man Called Otto movie and in analyzing the dataBased on the result of data analysis, the researcher found out four types of directive speech acts. The first type was commanding as the highest with 30 utterences. The second types was requesting with 28 utterances The third types was suggesting with 22 uttences. The last type was ordering. In conclusion, command was used to direct people or person to do something or do what the speaker wants, requesting was the expression of the speaker wants, request usually used in polite ways, suggestion was the opinion about what the addressee should or should not do from the speaker and in order, before do what the speaker wants, the listener will check the order of the speaker.